The Assertive Brain: Anterior Cingulate Phosphocreatine plus Creatine Levels Correlate With Self-Directedness in Healthy Adolescents - Squarcina, Letizia; Delvecchio, Giuseppe; Nobile, Maria; Mauri, Maddalena; Madonna, Domenico; Bonivento, Carolina; Garzitto, Marco; Piccin, Sara; Molteni, Massimo; Tomasino, Barbara; Bressi, Cinzia; Fabbro, Franco; et al. (Frontiers in Psychiatry, 2019)
Despite various advances in the study of the neurobiological underpinnings of personality traits, the specific neural correlates associated with character and temperament traits are not yet fully understood. Therefore, this study aims to fill this gap by exploring the biochemical basis of personality, explored with the temperament and character inventory (TCI), during brain development in a sample of adolescents. Twenty-six healthy adolescents (aged between 13 and 21 years; 9 males and 18 females) with behavioral and emotional problems underwent a TCI evaluation and a 3T single-voxel proton Magnetic Resonance Spectroscopy (¹H MRS) acquisition of the anterior cingulate cortex (ACC). Absolute metabolite levels were estimated using LCModel: Significant correlations between metabolite levels and selective TCI scales were identified. Specifically, phosphocreatine plus creatine (PCr+Cre) significantly correlated with Self-Directedness, positively, and with a self-transcendence (ST), negatively, while glycerophosphocholine plus phosphocholine (GPC+PC) and myo-inositol negatively correlated with ST. To the best of our knowledge, this is the first study reporting associations of brain metabolites with personality traits in adolescents. Therefore, our results represent a step forward for personality neuroscience within the study of biochemical systems and brain structures.